2006
DOI: 10.1007/s00442-006-0504-2
|View full text |Cite
|
Sign up to set email alerts
|

Divergent nonlinear responses of the boreal forest field layer along an experimental gradient of deer densities

Abstract: The early responses of the field layer to changes in biotic and abiotic conditions are key determinants of the future composition and structure of forests where sustained heavy browsing pressure has depauperated the shrub understory. We investigated the relationships between white-tailed deer density and field layer plant community dynamics in boreal forests managed for wildlife and timber production. We hypothesized that the growth and reproduction of field layer plants are either: (H(1)) directly proportiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
142
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 127 publications
(150 citation statements)
references
References 48 publications
6
142
1
1
Order By: Relevance
“…Our study used the infrastructure of an experiment on deer density control established in 2001 95 on sites with both intact and clearcut forested areas (Tremblay et al 2006). As plant responses in the 96 forests were slow (Hidding et al 2012), we chose to focus on clearcut areas in the current study.…”
Section: Experimental Design 94mentioning
confidence: 99%
“…Our study used the infrastructure of an experiment on deer density control established in 2001 95 on sites with both intact and clearcut forested areas (Tremblay et al 2006). As plant responses in the 96 forests were slow (Hidding et al 2012), we chose to focus on clearcut areas in the current study.…”
Section: Experimental Design 94mentioning
confidence: 99%
“…While several studies reported deer herbivory did not affect total herbaceous cover [8][9][10][11], these studies did not separately examine cover of forbs, graminoids, and ferns. As deer density and resulting herbivory intensity increases, the relative dominance of graminoids and ferns also increases [12][13][14] while decreasing the relative dominance of forbs [15,16]. Deer herbivory can accelerate the proliferation of invasive species, especially in conjunction with canopy disturbances that increase light to understory plants [17].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, higher densities of deer caused forests to be increasingly dominated by unpalatable tree species and understoreys to be increasingly dominated by ferns and grasses. In a similar, though shorter-duration, experiment in boreal forests of Quebec, Canada, Tremblay, Huot & Potvin (2006) recommended managing deer at densities < 7.5-15 deer km À2 for the conservation of browse-sensitive plants. While these studies come to similar conclusions about deer density thresholds, once these thresholds have been crossed, can forest communities recover?…”
Section: Introductionmentioning
confidence: 99%
“…While these studies come to similar conclusions about deer density thresholds, once these thresholds have been crossed, can forest communities recover? Based in part on guidance from these studies (Tilghman 1989;Horsley, Stout & deCalesta 2003;Tremblay, Huot & Potvin 2006, 2007, in some areas, deer are beginning to be managed at more sustainable levels (see e.g. Royo et al 2010;Tanentzap et al 2011).…”
Section: Introductionmentioning
confidence: 99%